Modeling The Characteristics Of Concrete With Different Aggregates* (Journal of Namibian Studies : History Politics Culture, 2023)
Here, in the present work combined effect of flaky aggregates and steel slag as partial replacement of coarse aggregate over the behavior of concrete prepared using marble powder as replacement of sand has been investigated. Two types of concrete mixes have been prepared by varying the ration of sand and marble powder which is 1:1 and 1:0.5. Using laboratory results a model has been developed to determine the compressive strength and slump values based on Percentage replacement of coarse aggregate, w/c ration, proportion of sand, marble powder, flaky aggregate and steel slag. The outputs produced by the model have been compared with the target outputs, which are the compressive strengths obtained experimentally.